Etnografia documental sobre as mortes maternas no estado do Amazonas: a precariedade e a desimportância da vida - Corrêa, Rachel Geber (2023)
In 2018, the state of Amazonas had the highest maternal death rate in Brazil, reaching a Maternal Mortality Ratio (MMR) of 108.4 per 100,000 inhabitants, being classified as high by the World Health Organization. In contrast to this rate, the Ministry of Health considers that most maternal deaths in Brazil are preventable and happen as a result of poor care and/or lack of access to health. Therefore, this work aims to analyze maternal deaths in 2018, in order to understand the phenomenon in the state of Amazonas. To achieve this objective, it was decided to carry out a documentary ethnography, using the content analysis of Laurence Bardin from 1977. The documentary sources of the research were the documents of the Maternal Mortality Committee of the municipality of Manaus and the Investigation Sheets of Deaths of the Municipal Health Secretariat (SEMSA) of Manaus, of the year 2018 and the publications in the Official Gazette of the State of Amazonas and in the Official Gazette of the Municipality of Manaus. The results obtained suggest the existence of an intersectionality of the vulnerabilities present in the lives of women who died in Manaus, demonstrated through the profile of maternal deaths, constructed by me from the maternal death investigation forms: the majority of women who died in 2018 registered in Manaus was black, resident of the east zone of Manaus, who underwent cesarean section, aged 30 to 45 years and who attended more than 06 prenatal consultations. In addition to the observed profile, this work demonstrated that the investigation of maternal death obeys a notary logic of completion and that there is a clear precariousness in the investigations of each process with the use of draft sheets, notes, illegible letters and, mainly, the absence of filling in essential fields to understand the history of women's death. Finally, the results demonstrated the absence of specific publications in the Official Gazettes for the prevention of maternal death that was ongoing throughout the year. In this sense, this dissertation demonstrates in the final considerations that there is a serious lack of filling in information about the investigation of death and that it is closely linked to the precariousness of life and vulnerability